De digitale brieveneditie als basis voor de studie van het tijdschrift Van Nu en Straks - Bert Van Raemdonck (Contextes)
The tradition of studying the journal Van Nu en Straks (1893-1894; 1896-1901) originates from the moment that the last issue was published. It has gone through several stages, each of which having their own characteristics. Recent research has been characterised by an interdisciplinary, contextualizing and comparatist approach. To be able to do such research, it is crucial that inventories of all relevant sources are taken and (recently dug up) sources are edited and published. In the XXIst century it seems that the most productive way to do so is by using electronic tools and devices. The time has come to create a digital corpus of letters in which researchers can find all sources they need to study Van Nu en Straks. In this essay I discuss some advantages and disadvantages to digital scholarly editions alongside some essential conditions which should be fulfilled to carry out such a digital project properly.